Boosting Customers’ Impulse Purchases through Trust - Aldiaz, Nail; Tuti, Meylani; Shahril, Aslinda Mohd (JDM (Jurnal Dinamika Manajemen), 2024)
This research aims to determine the influence of lifestyle, social media marketing, and customer reviews on trust and impulsive buying. The population in this study were fashion thrift buyers at x-brand stores. The sampling technique used was accidental sampling. The research results show a significant influence of lifestyle on impulsive buying and trust. Social media marketing affects trust, but not impulsive buying. Customer reviews on trust, but not on impulsive buying. Furthermore, trust influences impulsive buying. This shows that trust has a strong mediating influence that influences consumers to make impulsive purchases. This research has managerial implications since it offers thrift store business players new perspectives on how to encourage impulsive buying among consumers by giving them accurate and comprehensive information about the things they are selling. The findings of the study demonstrate that social media marketing, lifestyle, and customer reviews all enhance trust. Furthermore, there is no significant correlation between social media marketing and customer reviews and impulse buying, although lifestyle and beliefs do have a beneficial effect.